PELATIHAN GURU SD INPRES TIOM CARA MENGAJARKAN HITUNG DASAR MATEMATIKA DENGAN METODE JARIMATIKA DAN ALAT PERAGA - Amos Rombe; Mindo H. Sinambela; Barthon Wenda; Andinus Yanengga; Sutarman Borean (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2023)
Mathematics is one of the subjects that has been taught from the elementary level. However, in reality in the Papua Highlands area thats mathematics is still a problem for both students and teachers. Teachers who are used to teaching using the lecture method make students lazy to take math lessons which results in low math learning outcomes. Mathematics which has an abstract nature requires teachers to be able to concretize it so that it is easily understood by students, considering that students at the basic level are still classified as concrete thinkers. The purpose of implementing this PKM is to provide training for Inpres Tiom Elementary School teachers in creating a pleasant atmosphere for learning mathematics without having to burden students' brains, introduce methods that can be used to teach basic arithmetic, improve student learning outcomes, especially in fostering cooperation between Inpres Tiom Elementary School teacher partners with STKIP Abdi Wacana Wamena. Overcoming the problems above, a solution is provided so that the mathematics lessons being taught become fun lessons for elementary school children, partners are given learning training with the use of visual aids and the application of the jarimatics method. Based on the results of the evaluation of the training activities through the questionnaire provided, it was found that all the teachers who participated in the training strongly agreed with the training activities.